Pre preparation of kenaf/carbon PPL composite to be employed in selective laser sintering machine - Kiani, Golnar; Ibrahim, Rahinah; Abdan, Khalina (Faculty of Design & Architecture, Universiti Putra Malaysia, 2016)
Although many researchers have developed natural fibres as reinforcements for industrial composite materials, the available information regarding these natural fibres to be applicable in the Rapid Manufacturing (RM) system is insufficient. For RM systems and products, the main materials used are thermoplastic materials, epoxy resin, acrylonitrile butadiene styrene plastic and polyester materials. Natural and biodegradable composites provide important environmental advantages to the automotive industry, and sustainability, eco-friendliness. Hence obtaining green chemistry materials for RM system are the main objectives of this study for the development of bio-based industrial materials. To obtain stronger products, hybridisation of these so-called natural fibres with other fibres is necessary. Bio-composites employ polymers as matrices, resulting in lighter, stronger, and more cost-effective products that in some cases they can be melted, sintered, or solidified, similar to RM systems’ environment. The combination of Kenafbast fibres, a type of natural fibre, with polymer matrices results in satisfactory performance that can compete with synthetic fibre composites. Prior to test the designed material in the aimed RM system; which in this research is Selective Laser Sintering (SLS), tailoring and predicting its performance is necessary to avoid any high cost breakdown of RM machine due to usage of inappropriate consumables. Hence the present study aimed to evaluate the effect of special features of RM on Kenaf/carbon hybrid composites by performing the compression moulding of it insimilar temperature and sequence of Rapid Manufacturing of this designed material. Assessing the resulted properties, by means of tensile and shear strengths of the end products were of reasonable values compared with carbon or Kenaf/polymer matrices. Further study to process the same material in actual Selective Laser Sintering machine is suggested to obtain more accurate result.